The Oxford handbook of church and state in the United States - Davis, Derek (Oxford handbooks series, 2010)
Religious pluralism as the essential foundation of America's quest for unity and order / by Derek H. Davis -- Historical dimensions -- The founding era (1774-1797) and the constitutional provision for religion / by John F. Wilson -- Eighteenth-century religious liberty : the founding generation's Protestant derived understanding / by Barry Alan Shain -- Church and state in nineteenth-century America / by Steven K. Green -- Religious advocacy by American religious institutions : a history / by Melissa Rogers -- Constitutional dimensions -- Constitutional language and judicial interpretations of the free exercise clause / by Bette Novitt Evans -- The U.S. Supreme Court and non-First Amendment religion cases / by Ronald B. Flowers -- The meaning of the separation of church and state : competing views / by Daniel L. Dreisbach -- Managed pluralism : the emerging church-state model in the United States / by Nicholas Gvosdev -- Theological and philosophical dimensions -- Religious liberty and religious minorities in the United States / by Elizabeth A. Sewell -- Religious symbols and religious expression in the public square / by T. Jeremy Gunn -- Religious liberty as a democratic institution / by Ted G. Jelen -- Pursuit of the moral good and the church-state conundrum in the United States : the politics of sexual orientation beyond Lawrence / by Andrew R. Murphy and Caitlin Kerr -- Political dimensions -- Monitoring and surveillance of religious groups in the United States / by James T. Richardson and Thomas Robbins -- The U.S. Congress : protecting and accommodating religion / by Allen D. Hertzke -- The Christian Right and church-state issues / by Clyde Wilcox and Sam Potolicchio -- American religious liberty in international perspective / by John Witte, Jr. -- Sociological dimensions -- Supply-side changes in American religion : exploring the implications of church-state relations / by Roger Finke -- Peeking through Jefferson's wall : a sociological assessment of U.S. church-state relations / by N.J. Demerath III -- The role of civil religion in American society / by Richard V. Pierard -- Conclusion -- The interplay of law, religion, and politics in the United States / by Derek H. Davis